A method for preparing chitin nanocrystals by neutral periodate oxidation

Through the periodate oxidation method under neutral conditions, the problem of uneven product size and high cost in the traditional chitin nanocrystal preparation method is solved, and the preparation of chitin nanocrystals with high selectivity, low cost and high quality is achieved, with wide application prospects.

CN118580395BActive Publication Date: 2025-04-08RAW MATERIALS INTELLIGENT MANUFACTURING (WUHAN) NEW MATERIALS R&D CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410934194.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-04-08
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The traditional chitin nanocrystal preparation method has problems such as uneven product size and high preparation cost, making it difficult to achieve high selectivity, low cost, mild conditions, high yield and high quality preparation.

Method used

The periodate oxidation method under neutral conditions was adopted, and the pretreatment of alkali liquid, stirred oxidation reaction at room temperature, separation and purification were carried out to prepare chitin nanocrystals with high selectivity, low cost and high quality.

Benefits of technology

The high selectivity, low cost, mild conditions, high yield and high quality preparation of chitin nanocrystals is achieved. The product size is uniform, the water-based suspension is stable, and it has special volatile behavior and magnetic field reaction sensitivity characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580395B_ABST
    Figure CN118580395B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing chitosan nanocrystals by neutral periodate oxidation, and relates to the technical field of chitosan separation and extraction. The steps of the method include: soaking chitosan powder with alkali solution; mixing chitosan powder with periodic acid, and adjusting the pH of the reaction system to 6.5-7 with alkali solution; stirring at room temperature for oxidation reaction; centrifuging, ultrasonicating, and dialysis treatment of the reaction solution to obtain high-quality chitosan nanocrystals. The method provided by the present invention has the advantages of simple operation, high selectivity, mild reaction conditions, and high yield. The chitosan nanocrystal product prepared by the present method has uniform size and high stability, and has the particularity of volatile behavior and highly sensitive characteristics of magnetic field reaction. These characteristics will enable the chitosan nanocrystals prepared by the method of the present invention to be applied to more fields and have broader application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chitosan separation and extraction, and in particular to a method for preparing chitosan nanocrystals by oxidation with neutral periodate. Background Art

[0002] Chitosan is a natural polymer material that is widely found in the cell walls of crustaceans, insects and some microorganisms. Chitosan nanocrystals are highly ordered regions with compact molecular chains in chitosan. They have the advantages of good hydrophilicity, easy self-assembly, high strength, high specific surface area, high adsorption performance, high enhancement ability and biocompatibility. Therefore, the strategy of stripping chitosan nanocrystals from raw materials and utilizing them has great development potential. Rod-shaped chitosan nanocrystals are generally about 250nm long and about 10nm in diameter (derived from shrimp or crab shells) (Ling et al 2018). Chitosan nanocrystals not only have the physical and chemical properties of chitosan polymers, but also have the excellent characteristics of nanomaterials, such as: ultra-high specific surface area (Lin et al 2012); super strong structural strength (Deringer et al 2016); lightweight and high-strength materials (Huang et al 2016, Shamshina et al 2019); high biocompatibility; amphiphilic nanomaterials, etc. Therefore, chitosan nanocrystals are widely used in medicine, cosmetics, food, papermaking, lean oil and gas extraction, electronic display equipment, coatings, reinforcement materials and other fields.

[0003] Traditional chitosan nanocrystal preparation methods such as acidification, mechanical treatment, ion solution, partial deacetylation, and oxidation (TEMPO oxidation) have poor reaction selectivity, leading to problems such as uneven product size and high preparation cost. Therefore, the present invention provides a method for preparing chitosan nanocrystals using periodate under neutral conditions, which can achieve high selectivity, low cost, mild conditions, high yield, and high-quality chitosan nanocrystal preparation. Summary of the invention

[0004] In view of the deficiencies of the above prior art, the present invention provides a method for preparing chitosan nanocrystals by neutral periodate oxidation. The method uses mild and selectively oxidizable periodate as an oxidant under neutral conditions, and can achieve high selectivity, low cost, mild conditions, high yield, and high-quality preparation of chitosan nanocrystals.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] A method for preparing chitin nanocrystals by neutral periodate oxidation comprises the following steps:

[0007] (1) Soak chitosan powder in 2 wt.% to 4 wt.% alkali solution for three days. Alkali treatment can make the inside of chitosan swell and increase the internal gap of chitosan; after the alkali treatment is completed, centrifugation is required to remove the supernatant to eliminate the influence of organic matter generated during the alkali solution treatment on subsequent experiments, and the swollen chitosan is used for subsequent preparation.

[0008] (2) Mix the swollen chitosan, water, and periodic acid, and use alkali solution to adjust the pH of the reaction system to 6.5-7; at this time, the ion form of the periodate in the reaction system is H 4 I 2 O 10 2- The ion has a suitable negative charge and a large ionic radius. In a suitable electrostatic repulsion environment, the steric hindrance between the ion and the surface of the chitin crystal region is enhanced, resulting in better selectivity of the preparation system.

[0009] (3) The oxidation reaction is carried out by mixing and stirring at room temperature, and the reaction is terminated when the periodate concentration in the reaction solution drops below 12 g / L.

[0010] (4) Separating the reaction liquid to obtain a crude chitosan nanocrystal sample and an oxidized waste liquid.

[0011] (5) The chitosan nanocrystal coarse sample is ultrasonically treated to make it more dispersed, and the dispersed coarse sample is dialyzed. The sample is transferred into the dialysis bag after treatment and washing, and purified in ultrapure water. The water needs to be changed every day until the conductivity of the water is equal to or less than 0.4 μS / cm, and the dialysis is completed.

[0012] (6) The dialyzed chitosan nanocrystals are first subjected to ultrasonic treatment, and then centrifuged at 3000 r / min to remove large particles to obtain high-quality chitosan nanocrystals.

[0013] Preferably, the alkali solution in step (1) comprises KOH solution.

[0014] Preferably, the mass ratio of the swollen chitosan, water and periodic acid in step (2) is 1:(150-220):(3-11).

[0015] Preferably, the alkaline solution for adjusting pH in step (2) is aqueous ammonia or LiOH solution.

[0016] Preferably, the reaction time in step (3) is 9 to 15 days.

[0017] Preferably, the separation in step (4) is carried out using a centrifuge at 6000 rpm.

[0018] Preferably, the molecular weight cut-off of the dialysis bag used in the dialysis process in step (5) is 14000Da.

[0019] Compared with the prior art, the present invention is beneficial in that:

[0020] (1) The method provided by the present invention uses periodic acid and reacts at room temperature and neutral pH conditions, thereby avoiding the severe damage to the chitin structure by traditional methods and the corrosiveness of the reaction solution. The prepared chitin nanocrystals have a length of 137-183 nm and a diameter of 6-10 nm, and the product size is uniform.

[0021] (2) The method provided by the present invention obtains chitin nanocrystals through alkaline solution pretreatment, neutral periodate oxidation, separation and purification. The method is simple to operate and has the advantages of high selectivity, mild reaction conditions, high yield, etc., and is more conducive to the large-scale preparation of chitin nanocrystals.

[0022] (3) The chitosan nanocrystals prepared by the method of the present invention have a water-based suspension that can remain stable for a long time and have the peculiarity of volatilization behavior and high sensitivity to magnetic field response. These characteristics will enable the chitosan nanocrystals prepared by the method of the present invention to be applied to more fields, such as nanoelectronics, drug delivery, intelligent optics, etc., and have broader application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart of the preparation of chitosan nanocrystals of the present invention;

[0024] Figure 2 TEM image of chitosan nanocrystals prepared in Example 1;

[0025] Figure 3 This is the state of the chitosan nanocrystal suspension after being left for 1 hour; Figure 3 A is the chitosan nanocrystal prepared in Example 1; Figure 3 B is chitin nanocrystals prepared by traditional acid hydrolysis method; Figure 3 C is chitosan nanocrystal prepared by the method described in invention patent CN 112513102 A;

[0026] Figure 4 It is the volatilization behavior of chitin nanocrystal suspension; Figure 4 A is the chitosan nanocrystal prepared in Example 1; Figure 4 B is chitin nanocrystals prepared by traditional acid hydrolysis method;

[0027] Figure 5 Comparison of the volatilization time of chitin nanocrystal suspension;

[0028] Figure 6This is the reaction of the chitosan nanocrystal suspension prepared in Example 1 under a 0.3T magnetic field. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a method for preparing chitosan nanocrystals by neutral periodate oxidation, comprising the following steps:

[0031] (1) Soak chitosan powder in 2 wt.% to 4 wt.% alkali solution for three days. Alkali treatment can make the inside of chitosan swell and increase the internal gap of chitosan; after the alkali treatment is completed, centrifugation is required to remove the supernatant to eliminate the influence of organic matter generated during the alkali solution treatment on subsequent experiments, and the swollen chitosan is used for subsequent experiments.

[0032] (2) Mix the swollen chitosan, water, and periodic acid, and use alkali solution to adjust the pH of the reaction system to 6.5-7; at this time, the ionic form of periodate in the reaction system is H 4 I 2 O 10 2- The ion has a more suitable negative charge and a large ionic radius, which enhances the electrostatic repulsion and steric hindrance between the ion and the surface of the chitin crystal region, resulting in better selectivity of the preparation system.

[0033] (3) The mixture is mixed and stirred at room temperature to carry out an oxidation reaction, and the reaction is terminated when the periodate concentration in the reaction solution drops below 12 g / L.

[0034] (4) Separating the reaction liquid to obtain a crude chitosan nanocrystal sample and an oxidized waste liquid.

[0035] (5) The chitosan nanocrystal coarse sample is ultrasonically treated to make it more dispersed, and the dispersed coarse sample is dialyzed. The sample is transferred into the dialysis bag after treatment and washing, and purified in ultrapure water. The water needs to be changed every day until the conductivity of the water is equal to or less than 0.4 μS / cm, and the dialysis is completed.

[0036] (6) The dialyzed chitosan nanocrystals are first subjected to ultrasonic treatment, and then centrifuged at 3000 r / min to remove large particles to obtain high-quality chitosan nanocrystals.

[0037] In some examples, the alkaline solution in step (1) includes a KOH solution.

[0038] In some examples, the mass ratio of the swollen chitosan, water, and periodic acid in step (2) is 1:(150-220):(3-11).

[0039] In some examples, the alkaline solution for adjusting the pH in step (2) is aqueous ammonia or LiOH solution.

[0040] In some examples, the reaction time in step (3) is 9 to 15 days.

[0041] In some examples, the separation in step (4) is performed using a centrifuge at 6000 rpm.

[0042] In some examples, the molecular weight cutoff of the dialysis bag used in the dialysis process in step (5) is 14,000 Da.

[0043] In the following implementation, the periodic acid, potassium hydroxide, lithium hydroxide, ammonia water and chitosan powder used were purchased from MacLean Reagent Company.

[0044] Example 1

[0045] This embodiment provides a method for preparing chitosan nanocrystals by neutral periodate oxidation, comprising the following steps:

[0046] (1) Soak chitosan powder in 2 wt.% KOH solution for three days. Alkali treatment can make the inside of chitosan swell and increase the internal gap of chitosan; after the alkali treatment, centrifuge at 3000r / min for 10min to remove the supernatant, eliminate the influence of organic matter produced during the alkali solution treatment on subsequent experiments, and use the swollen chitosan for subsequent experiments.

[0047] (2) Mix 1 g of swollen chitin, 180 mL of pure water, and 7 g of periodate oxidation solution, and adjust the pH of the reaction system to 7 using ammonia water and LiOH solution; at this time, the ion form of periodate in the reaction system is H 4 I 2 O 10 2- The ion has a suitable negative charge and a large ionic radius, which enhances the electrostatic repulsion and steric hindrance between the ion and the surface of the chitin crystal region, resulting in better selectivity of the preparation system.

[0048] (3) The oxidation reaction was carried out by mixing and stirring at room temperature for 12 days, and the reaction was terminated when the periodate concentration in the reaction solution dropped to 12 g / L.

[0049] (4) The reaction solution was placed in a centrifuge and centrifuged at 6000 rpm for 10 min to obtain a crude chitosan nanocrystal sample and oxidized waste liquid.

[0050] (5) The chitosan nanocrystal crude sample is ultrasonically treated to make it more dispersed, and the dispersed crude sample is dialyzed. The sample is transferred into the dialysis bag using a cleaned 14000Da dialysis bag and purified in ultrapure water. The water needs to be changed every day until the water conductivity is equal to 0.4μS / cm, and the dialysis is completed.

[0051] (6) The dialyzed chitosan nanocrystals were first subjected to ultrasonic treatment, and then centrifuged at 3000 r / min for 10 min to remove large particles, thereby obtaining high-quality chitosan nanocrystals. The separation results are shown in Table 1.

[0052] Comparative Example 1

[0053] The method for preparing chitosan nanocrystals in this comparative example is basically the same as that in Example 1, except that in this comparative example, NaOH solution is used to adjust the pH of the reaction system to 7, and KOH solution is used to adjust the pH of the reaction system to 7. The separation results are shown in Table 1.

[0054] Comparative Example 2

[0055] The method for preparing chitosan nanocrystals in this comparative example is basically the same as that in Example 1, except that ammonia water is used in this comparative example to adjust the pH of the reaction system to 10. The separation results are shown in Table 1.

[0056] Table 1: Separation results of Example 1 and Comparative Examples 1-2

[0057]

[0058] As can be seen from Table 1, under the same conditions, the chitosan nanocrystals are prepared with different alkali solutions and different pH values, and the yields of chitosan nanocrystals are very different. In Example 1, the chitosan nanocrystals are prepared by adjusting the pH of the reaction system to 7 using ammonia water and LiOH solution, and the yields of chitosan nanocrystals are all above 40%; while in Comparative Example 1, the chitosan nanocrystals are prepared by adjusting the pH of the reaction system to 7 using NaOH solution and KOH solution, and no obvious product is generated; and the chitosan nanocrystals are prepared by adjusting the pH of the reaction system to 10 using ammonia water, and only very few products are generated.

[0059] Figure 2 TEM image of chitosan nanocrystals prepared in Example 1. TEM image shows that chitosan nanocrystals prepared by the method of the present invention are rod-shaped results with relatively uniform size, with a length of 137-183nm and a diameter of 6-10nm. Table 2 shows the size distribution of chitosan nanocrystals prepared by different methods.

[0060] Table 2: Size distribution of chitin nanocrystals prepared by different methods

[0061]

[0062] Stability test of chitosan nanocrystal suspension: 10 mg of chitosan nanocrystals were mixed with 1 mL of water to form a suspension, and the stability of the chitosan nanocrystal suspension was observed. Figure 3 The state of the chitosan nanocrystal suspension after being placed for 1 hour, wherein 3A is the chitosan nanocrystal prepared by the method of the present invention; 3B is the chitosan nanocrystal prepared by the traditional acid hydrolysis method (heating and stirring HCl solution at 104°C); 3C is the chitosan nanocrystal prepared by the invention patent CN 112513102 A. The test results show that after the chitosan nanocrystal suspension is placed for 1 hour, the bottom of the chitosan nanocrystal suspension prepared by the traditional acid hydrolysis method gradually solidifies to form a gel state that cannot flow; the chitosan nanocrystal suspension prepared by the method described in the invention patent CN 112513102 A precipitates; while the chitosan nanocrystal suspension prepared by the method of the present invention maintains its original state without solidification and sedimentation, indicating that the chitosan nanocrystal prepared by the method of the present invention can be stably present in water for a long time.

[0063] Volatilization behavior test of chitosan nanocrystal suspension: The chitosan nanocrystal suspension prepared by the method of the present invention is placed in a capillary. During the evaporation and drying process of the chitosan nanocrystal suspension, the suspension will be fixed at the end of the capillary and gradually dry into the tube (such as Figure 4 A), regular birefringence color formation can be observed under a microscope. However, the chitin nanocrystal suspension prepared by the traditional acid hydrolysis method forms a large number of crystal-like aggregates in the capillary (such as Figure 4 B), no regular birefringence fringes can be formed. In addition, the evaporation time of the chitin nanocrystal suspension in the capillary (as shown in Figure 5 As shown in the figure, it takes about 3 hours for the suspension of chitosan nanocrystals prepared by the method of the present invention to be completely dried, while it takes about 60 hours for the suspension of chitosan nanocrystals prepared by the traditional acid hydrolysis method to be completely dried.

[0064] Reaction of chitosan nanocrystal suspension under magnetic field: The chitosan nanocrystal suspension prepared by the method of the present invention can form specific patterns (such as Figure 6 As shown in the figure, the suspension of chitin nanocrystals prepared by traditional acid hydrolysis method cannot form similar textures under the same magnetic field.

[0065] In summary, the method provided by the present invention has the advantages of simple operation, high selectivity, mild reaction conditions and high yield. The chitosan nanocrystals prepared by the method of the present invention are of high quality, which is specifically manifested in that the product size is uniform and the water-based suspension can remain in a stable state for a long time. In addition, the chitosan nanocrystals prepared by the method of the present invention not only have the physicochemical properties of chitosan polymers and the excellent properties of nanomaterials, but also have the particularity of volatilization behavior and the highly sensitive characteristics of magnetic field response. These characteristics will enable the chitosan nanocrystals prepared by the method of the present invention to be applied to more fields and have broader application prospects.

[0066] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A method for preparing chitosan nanocrystals by neutral periodate oxidation, characterized in that: The following steps are involved: (1) soaking chitosan powder in alkali solution to obtain swollen chitosan powder; (2) Mix the swollen chitosan powder, water, and periodic acid, and adjust the pH of the reaction system to 6.5-7 using ammonia water or LiOH solution; (3) stirring at room temperature to carry out oxidation reaction; (4) subjecting the reaction solution to centrifugation, ultrasound, and dialysis treatment; (5) The chitosan nanocrystals after the dialysis treatment are subjected to ultrasonic and centrifugal treatment to obtain chitosan nanocrystals.

2. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: After the soaking in step (1), the soaked chitosan powder needs to be centrifuged to remove the supernatant.

3. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: The alkali solution in step (1) includes KOH solution.

4. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: The concentration of the alkali solution in step (1) is 2wt.% to 4wt.%.

5. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: The soaking time in step (1) is 3 days.

6. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: The mass ratio of the swollen chitosan powder, water and periodic acid in step (2) is 1:(150-220):(3-11).

7. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: After adjusting the pH of the reaction system in step (2), the ion form of the periodate in the reaction system is H4I2O 10 2- .

8. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: The oxidation reaction time in step (3) is 9 to 15 days.

9. The method for preparing chitosan nanocrystals by neutral periodate oxidation according to claim 1, characterized in that: During the dialysis treatment in step (4), water needs to be replaced until the conductivity of the water is equal to or less than 0.4 μS / cm.

Citation Information

Patent Citations

  • Method for isolating cellulose- or chitin-nanocrystals by means of periodate oxidation

    CN112513102A

  • Method for Isolating Cellulose- or Chitin-Nanocrystals by Means of Periodate Oxidation

    US20210108003A1